FRI0075 The Impact of Comorbidity on Functional Status in RA, 10 Years from Disease-Onset. Results from Two Large Uk Inception Cohorts. (9th June 2015) - Nikiphorou, E.; Norton, S.; Demetriou, C.; Dixey, J.; Prouse, P.; Kiely, P.; Walsh, D.A.; Young, A.
Abstract : Background: Comorbidities in Rheumatoid Arthritis (RA) can have a negative impact on functional ability. However, the extent of this impact is less well understood, especially in established disease. In the absence of a standardised and validated tool for comorbidity data collection, understanding which comorbidities at the early stages of disease have the greatest impact on functional outcomes is important in terms of preserving functional status and optimising disease management. Objectives: To examine the effect of comorbidities by the first year of RA on 10-year functional status using the health assessment questionnaire (HAQ). Methods: Data from two multi-centre (n=32) UK inception cohorts (1986-2013), the Early RA Study and Early RA Network (total n=2701) were used. DMARD-naïve patients were recruited at presentation and standard clinical, laboratory and radiographic variables recorded at baseline and yearly thereafter. Date and cause of death was provided by the Medical Research Information Service. The presence of comorbidities and extra-articular manifestations was recorded at individual disease level. These were grouped into the standard ICD10 systems (n=15) and further subdivided by severity, e.g. cardiovascular major (ischaemic heart disease, cardiac failure) or minor (benign cardiac arrhythmias). Multivariate Cox regression analysis adjusting for age at disease onset, gender, baseline HAQ, BMI and presence of rheumatoid factor and recruitment year was used, with HAQ as the outcome at year 10. HAQ was examined as a binary outcome using the median HAQ at 10 years (1.13) as the cut-off since HAQ distribution did not allow for it to be treated as continuous in linear or generalized linear models. Results: Of the patients with HAQ scores available at year 10, 189 and 99 patients had at least one major and one minor comorbidity respectively recorded by the first year of disease (1yr prevalence: 26.3% and 13.8%). Higher HAQ at 10yrs was significantly predicted in separate models by major respiratory comorbidities (HR 1.29, 95% CI 0.99-1.66, p=0.05) and major spinal disease (HR 2.03, 95%CI 1.08-3.09, p=0.026). Major respiratory disease included bronchiectasis and chronic obstructive pulmonary disease (COPD) and major spinal disease included C-spine subluxation, spinal stenosis and slipped disc disease with neurological compromise. At individual disease level, COPD was found to be the only significantly predictive comorbidity for higher HAQ at 10yrs (HR 1.48, 95% CI 1.08-2.01; p=0.013). Conclusions: Co-existent major respiratory and spinal diseases are significant predictors of functional status at 10yrs from disease-onset in RA. At individual disease level, COPD predicted higher HAQ at 10yrs, highlighting its impact together with conventional measures of RA severity on functional status. Targeting and closely managing these conditions is therefore important in terms of long-term functional outcomes in RA. Acknowledgements: We are indebted to all the nurses and rheumatologists from both cohorts for their participation and contribution to the study. Disclosure of Interest: None declared